Implementation of The 'Talaqiyyan Fikriyyan' Method in Fostering Religious And Moral Aspects in Early Childhood at Al-Akram Early Childhood Education - Suharyani, Suharyani; Lestari, Gunarti Dwi; Hariyati, Nunuk (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2025)
This research aims to explore the application of the "TalaqiyyÄn FikriyyÄn" method in developing moral and religious aspects in early childhood at PAUD Al-Akram. Through a systematic research method focused on collecting valid qualitative data, it is expected to make a significant contribution to the understanding and practice of religious education for young children. The TalaqiyyÄn FikriyyÄn method, which focuses on the integrative instillation of moral and religious values through a reflective thinking approach, is anticipated to provide a strong foundation for character formation in children. This approach emphasizes not only memorization but also a deep understanding that aligns with the cognitive development level of early childhood. This study employs a qualitative approach with a case study method, where data is obtained through observations, interviews with educators, and documentation of learning activities at PAUD Al-Akram. The results indicate that the application of the TalaqiyyÄn FikriyyÄn method is effective in fostering children's basic understanding of moral and religious concepts, such as honesty, responsibility, and respect for others. Additionally, this method enhances children's motivation to apply these values in their daily lives through enjoyable and interactive learning experiences. The implications of this research suggest that the TalaqiyyÄn FikriyyÄn method has great potential to be implemented in other early childhood education institutions to support the formation of good character from an early age. This research produces outputs in the form of: (1) a scientific publication in a nationally accredited Sinta 4 journal that describes data on the implementation of the TalaqiyyÄn FikriyyÄn method in developing early childhood capabilities in the aspects of religious and moral values; (2) a "TalaqiyyÄn FikriyyÄn" learning model that can be applied to develop all aspects of child development at PAUD Al-Akram